2013
DOI: 10.1177/0897190013515709
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Community Pharmacists and Final-Year Student Pharmacists and their Perception of Psychotherapeutic Agents

Abstract: Final-year student pharmacists would benefit from the curricular incorporation of courses and advanced pharmacy practice experiences in Psychiatry. Community pharmacists caring for customers with psychiatric disorders should take advantage of continuing education series that highlight updates and new developments regarding psychotherapeutic agents in order to improve clinical outcomes of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Among published studies, MHK was operationalized in various ways including focusing on identifying medications or specific mental illnesses and recognizing recommended interventions. 24,29 These knowledge studies are limited as they do not include other important issues such as disease prevalence, mental illness symptomology, or information regarding untreated mental illness outcomes, all of which are important when treating these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among published studies, MHK was operationalized in various ways including focusing on identifying medications or specific mental illnesses and recognizing recommended interventions. 24,29 These knowledge studies are limited as they do not include other important issues such as disease prevalence, mental illness symptomology, or information regarding untreated mental illness outcomes, all of which are important when treating these patients.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that most respondents strongly disagreed or disagreed with the statements that ‘The pharmacy undergraduate curriculum addresses explicitly mental health and common mental disorders’ and ‘The pharmacy curriculum prepares one adequately to practice psychiatry pharmacy’. This finding contradicts studies among pharmacy students in a Florida University and practising community pharmacists in North Carolina . In the North Carolina study, many of the practising pharmacists reported mental health as part of their didactic course work.…”
Section: Discussionmentioning
confidence: 59%
“…4 These factors combined make pharmacists' involvement in mental health care more pertinent now than ever before. 4,5 Studies in developed countries show that despite the large volume of prescriptions of medications for mental health disorders filled in pharmacies on daily basis, pharmacists have inadequate training in mental health disorders, little knowledge of antipsychotic medicines 6,7 and are not comfortable providing pharmaceutical care services for patients with mental health disorders. 8,9 This evidence indicates an urgent need to re-evaluate the training of pharmacists in relation to mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 survey by McKee and colleagues highlights mood stabilizer knowledge as a deficit among pharmacists. 20 A recent study indicated that pharmacists felt less comfortable delivering patient counseling for mental-health related medications when compared with cardiac medications. 21 To increase their comfort level with psychiatric illnesses, PCMH-based pharmacists could consider shadowing psychiatric pharmacists, attending continuing education on psychiatry focused topics, or even attending psychiatry-focused meetings to stay up-to-date and informed.…”
Section: Discussionmentioning
confidence: 99%